The The Role of Parents in Developing 5-6 Years Children's Self-Control - Maghfirota Auriza; Adriani Rahma Pudyaningtyas; Anjar Fitrianingtyas (Universitas Negeri Semarang, 2023)
This study aimed to (1) describe 5-6 years of children’s self-control development at Dusun Mangunrejo RW 12, (2) describe the role that parents took during the self-control development process, also (3) describe support and obstacle factors that parents felt during children’s self-control development process. This research was ethnography research with an ethnomethodological approach. Informants in this research were ten parents that have 5-6 years of children with random cluster sampling as a sampling technique. The results showed that 5-6 years of children’s self-control development were pretty good. Children’s development indicated that they could do 6-8 form 8 points in 5 – 6 years developmental self-control stage. Parent’s role in helping develop children’s self-control was education and guidance. Many support and obstacle factors were found during educating and guiding processes.